2006
DOI: 10.1186/1477-7525-4-41
|View full text |Cite
|
Sign up to set email alerts
|

Public telesurveillance service for frail elderly living at home, outcomes and cost evolution: a quasi experimental design with two follow-ups

Abstract: Background: Telesurveillance is a technologically based modality that allows the surveillance of patients in the natural setting, mainly home. It is based on communication technologies to relay information between a patient and a central call center where services are coordinated. Different types of telesurveillance systems have been implemented, some being staffed with non-health professionals and others with health professional, mainly nurses. Up to now, only telesurveillance services staffed with non-health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
15

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 22 publications
2
35
0
15
Order By: Relevance
“…Two related studies of a medic-alert device found it increased caregivers’ sense of security and decreased their sense of burden. 36, 44 Four studies looked exclusively at AT for individuals with cognitive impairment. The AT that was investigated included a day/night clock, 29,33,43 lost item locator, 33 automatic nightlight, 33 gas cooker device, 33 and a picture button telephone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two related studies of a medic-alert device found it increased caregivers’ sense of security and decreased their sense of burden. 36, 44 Four studies looked exclusively at AT for individuals with cognitive impairment. The AT that was investigated included a day/night clock, 29,33,43 lost item locator, 33 automatic nightlight, 33 gas cooker device, 33 and a picture button telephone.…”
Section: Resultsmentioning
confidence: 99%
“…None of the intervention studies described the characteristics of participants lost to follow-up. Fourteen studies 13,16,29–32,36,3840,42,4445 did not explicitly define the caregivers they included and eight 11,13,2728,32, 3435,38 relied on care recipients’ perceptions in order to establish caregivers’ outcomes. None documented the usage frequency of the AT being studied in any manner.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 A recent study has shown satisfaction to be far higher with this type of service compared with other services such as home care, not only among the elderly but also among their caregivers, because telemedicine appears to have a positive impact on their stress and on anxiety concerning the health of their elderly relation. 11 The primary aim of this study was to assess the level of satisfaction with 3 types of formal care systems: the day care center, the nursing home, and telecare in a group of frail oldest elderly, and to describe the characteristics of the population using the services.…”
Section: Introductionmentioning
confidence: 99%